The Influence Of Education And Career Development On Employee Performance At PT. Dian Swastatika Sentosa Tbk Karawang - Natasha Cecilia Deviagisti; Sari Marliani; July Yuliawati (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — This research aims to analyze the influence of education and career development on employee performance at PT Dian Swaistika Sentosa Tb Research method— This research used descriptive quantitative verification methods with SPSS version 25 and multiple linear regression analysis, involving 61 respondents Result— The results of the research show that the education variable gets a pretty good score, career development gets a pretty good score and performance gets a pretty good score. Partially, the education variable (X1) has no effect on performance, while the career development variable (X2) has a significant effect on performance. Simultaneously, both educational variables (X1) and career development (X2) have a significant effect on performance Conclusion— The findings suggest that career development is a key factor influencing employee performance, while education alone does not significantly impact performance. The practical implication is that the company should focus on providing effective career development programs to improve overall employee performance